2006
DOI: 10.1038/sj.bdj.4813468
|View full text |Cite
|
Sign up to set email alerts
|

Revalidation of general dental practitioners in Scotland: The results of a pilot study Part 2 – acceptability to practitioners

Abstract: AimTo investigate the acceptablility of a pilot scheme of revalidation to general dental practitioners. Method Ten general dental practitioners completed portfolios of evidence of being up to date and fit to practise. This portfolio was assessed by a panel of three experts, using an assessment tool developed specifically for that purpose. An action research methodology was used to evaluate participants' perceptions, consisting of a focus group and semi-structured interviews. The views of the assessors on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
1
2
0
2
Order By: Relevance
“…The students and mentors were also asked about how the three components of the strategy influenced their understanding of the reflective process and achievement of its outcomes during the experience. There was agreement between students and mentors regarding the importance of discussion and interaction for reflection—both with a mentor, as previously reported by Henderson et al, 23 Driessen et al, 26 Maidment et al, 27 and Bush and Bissell, 21 and with peers, as reported by Harris 22 and Koole et al 11 Discussion was considered a tool aimed at helping orthodontic students in the reflective process and particularly in the achievement of the outcomes of reflection.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The students and mentors were also asked about how the three components of the strategy influenced their understanding of the reflective process and achievement of its outcomes during the experience. There was agreement between students and mentors regarding the importance of discussion and interaction for reflection—both with a mentor, as previously reported by Henderson et al, 23 Driessen et al, 26 Maidment et al, 27 and Bush and Bissell, 21 and with peers, as reported by Harris 22 and Koole et al 11 Discussion was considered a tool aimed at helping orthodontic students in the reflective process and particularly in the achievement of the outcomes of reflection.…”
Section: Discussionsupporting
confidence: 70%
“…They cautioned that using a portfolio provides no guarantee that reflection will actually occur and suggested that the conditions for successful reflective use of portfolios were coaching, structure and guidelines, experience and materials, and summative assessment of reflection. The lack of agreement on a portfolio's ability to stimulate reflection was also evident in the dentists’ perceptions collected in a focus group study by Maidment et al 27 Dentists and assessors in that study noted that the conditions for effective use of portfolio as a reflective tool were support, training, flexible design of portfolio, and system of appraisal.…”
mentioning
confidence: 95%
“…In nursing education, articles have focused on portfolio development, 19,20 pros and cons of implementation, 5 models of portfolios, 21 evaluation, 22,23 and portfolio use for summative and formative assessment. In dental education, portfolios have been recommended during initial licensure, 24 proposed for continuing professional development, 25 utilized during licensure revalidation, 26 and used to assess competency in dental hygiene programs. 27 Portfolios can offer multiple sources of data, thereby increasing both reliability and validity in the licensure process.…”
Section: Portfolio Use In Contextmentioning
confidence: 99%
“…Beaucoup d'auteurs [8,[25][26][27][28][29] considèrent le temps comme un facteur ayant une influence négative sur l'utilisation de portfolios par les professionnels de santé, qui éprouvent des difficultés à ajouter l'élabo-ration d'un portfolio dans un emploi du temps déjà chargé. Kjaer et al [12] doutent de la possibilité d'inté-grer 10 à 15 minutes de temps alloué protégé supplé-mentaire dans le cadre du dispositif de rencontre formateur/stagiaire déjà en place.…”
Section: Tempsunclassified
“…Dagley et Berrington [28] ont constaté que certains dossiers documentaient d'authentiques démarches de réflexivité de la part de leurs utilisateurs, comme l'attestaient des liens électroniques avec les incidents critiques enregistrés dans leur pratique, leur PDP et les activités de DPC. L'étude en deux parties de Maidment et al [7,8] a également rapporté le potentiel des portfolios pour soutenir la pratique réflexive. Parmi les dix participants cependant, il a été signalé que la pratique réflexive pouvait se développer indé-pendamment et que, par conséquent, les portfolios pouvaient être une contrainte artificielle et inutile.…”
Section: Promouvoir La Réflexivitéunclassified